Respuesta :

Answer:

(x + 1)² + (y - 1)² = 16

Step-by-step explanation:

Since the standard form for an equation of a circle is

(x - h)² + (y - k)² = r²

The (h,k) are co-ordinate of your centre of circle, which in this case is (-1,1) and r is the radius of circle.

As we can see in the figure radius = 4units

from centre(1,-2) to (1,-2)

Put these into the equation

(x + 1)² + (y - 1)² = 4²

(x + 1)² + (y - 1)² = 16

Answer:

The equation of the circle is:

              [tex](x+1)^2+(y-1)^2=4^2[/tex]

                           or

                [tex]x^2+y^2+2x-2y=14[/tex]

Step-by-step explanation:

The radius of the given circle as represented in the graph is: 4 units.

The center of a circle is: (-1,1)

We know that the equation of a circle with center (h,k) and radius r is given by:

[tex](x-h)^2+(y-k)^2=r^2[/tex]

We have:

r=4 and (h,k)=(-1,1)

Hence, the equation of circle is:

[tex](x+1)^2+(y-1)^2=4^2\\\\\\x^2+1+2x+y^2+1-2y=16\\\\x^2+y^2+2x-2y=14[/tex]

              Hence, equation is:

            [tex](x+1)^2+(y-1)^2=4^2[/tex]

                           or

                [tex]x^2+y^2+2x-2y=14[/tex]

ACCESS MORE